Regional specialisation in a transition country - Hungary - Mary Rédei (European Regional Science Association (ERSA), 2001)
There has been a growing interest on regional issue over the last decade stimulated by increasing policy about reducing regional inequalities resulted from economic integration. In the last decade the free trade affected the post-communist countries, and predominantly among them those, which had a maturated level of stability, economical development and their geopolitical situation is favoured. Hungary is a considerable area to study the pattern of “new economic geography”. In paper we identify, explain and forecast the impact of globalisation, on regional and small unit /local level. The key question for the future development of the world economy is how will the economy choose its new place? Are regional inequalities likely to narrow or widen? And how the EU enlargement likely to lead to the relocation of industries? The regional indicators are verifying on NUTS level III. the regional concentration and describe the shifted new regional structure. The aim of the project to check the regularities and irregularities of the variables in an accession country. The relevant findings will be discussed concerning the policy. The questions to be addressed, which changes may be identified due to the trade reorientation towards the EU? Which new location an relocation of industrial activity may be identified? What types of regions are likely to be winners and losers who regulate the regulators? About the adaptation process we will draft some policy orientation for decision makers.
Keywords: 330